Fatores associados a adesão ao curso de capacitação a distância para líderes, voluntários, profissionais e gestores de Comunidades Terapêuticas - Oliveira, Giovana Carvalho de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Introduction: It is estimated that in Brazil 80% of the care to people with alcohol, crack and other drugs problems take place in Therapeutic Communities (TC), hence the importance given to this type of facility by alcohol and other drugs policies drugs, especially the Program Crack - we can win.The expansion of the number of TCs in Brazil and the diversity of its staff constitution and approaches led SENAD, in partnership with FMB-UNESP, to organize a training course addressed to managers, workers and volunteers connected with TCs. Objective: To identify factors associated with adherence to a free online course aimed at training professionals, therapists, volunteers, managers and leaders of TCs dealing with alcohol, crack and other drugs dependents. Methods: This is a longitudinal evaluation, quantitative study of 7,572 students enrolled in the training course who agreed to participate, between December 2014 and July 2015 Results: Out of the 7,572 enrolled subjects, 2,963 (39.1%) withdrew before the final exam and 4,609 (60.9%) did the final exam. The rate of completion among those working in a TC was 64.9%, as compared to 57.1% among other enrolled students (p<0.001). Professional status was significantly associated with completion rate: 70.1% of managers, 66.4% of other workers and 61.8% of volunteers completed the course. In the final logistic regression model, Outcome withdrawal was associated with the following factor: Black/Brown color (all subjects), never had used Moodle, not having had any continuing education course on substance use in the last two years and being from the Center West Region (only for subjects not connected with a TC) and not having completed a training course on Substance use prevention - a course for county counsellors (only for those working in TCs) whereas Outcome final exam was associated with age (36 years and over, for all enrolled students). Conclusion: It can be concluded that being a TC ...

Introdução: Estima-se que, no Brasil, 80% da atenção aos usuários de álcool, crack e outras drogas ocorrem em Comunidade Terapêuticas (CTs) e é por este motivo que as políticas de enfrentamento ao uso nocivo de álcool, crack e outras drogas, e o Programa Crack, é possível vencer, reconhecem a importância deste dispositivo. A expansão do número de CTs e a diversidade de constituição da equipe e métodos utilizados levaram a SENAD, em parceria com FMB-UNESP, a organizarem um curso para trabalhadores de CTs. Objetivo: Identificar os fatores associados à adesão de profissionais, terapeutas, voluntários, gestores e líderes de Comunidades Terapêuticas a um curso de capacitação a distância. Métodos: Trata-se de um estudo longitudinal, de avaliação quantitativa de 7.572 alunos matriculados no curso que consentiram em participar desse estudo, entre dezembro de 2013 e julho de 2014. Foi utilizado um questionário específico para a obtenção dos dados. Resultados: Dos 7.572 alunos 2.963 (39,1%)abandonaram o curso.Quanto à adesão, neste estudo 4.609 (60,9%) dos alunos concluíram o mesmo.A taxa de concluintes entre os trabalhadores de CT foi de 64,9% (N= 2.384) contra 57,1% dos demais alunos (p<0,001). A posição profissional na CT influiu na adesão e certificação: 70,1% dos gestores foram certificados, 66,4% dos funcionários e 61,8% dos voluntários. No modelo final de regressão logística, o desfecho abandono se associou aos seguintes fatores: cor negra/parda (para todos os alunos); nunca ter utilizado a plataforma Moodle, não ter realizado nenhum curso de atualização em dependência química nos últimos dois anos e ser proveniente da região Centro Oeste (apenas para alunos que não eram de CT) e não ter realizado o curso de Prevenção ao uso indevido de drogas: curso de capacitação para conselheiros municipais (apenas para alunos que trabalhavam em CTs), ao passo que o desfecho...
Keywords: Ensino a distância; Comunidade terapeutica - Estudos longitudinais; Profissionais; Voluntários; Professional employees